Public Behaviour on Cash Waqf: Evidence from Indonesia - Haidlir, Banu M; Laksmono, Bambang S; Kasri, Rahmatina A; Azizon, Azizon; Hartono, Djoni (Universitas Negeri Semarang, 2021)
Despite the potential governmental agenda towards cash waqf, this area has been givessn limited attention in academic literature with special regards to the supply side. Therefore, this study aims to investigate the factors influencing the public intention in endowing cash waqf by utilizing an extended theory of planned behaviors (TPB); in which religiosity, knowledge, and trust variables are added. Primary data from 685 respondents in Indonesia are analyzed using structural equation modeling (SEM). The result showed that the intention to endow cash waqf is positively affected by all of the TPB variables (attitude, subjective norms, and perceived behavioral control) and other extended variables. The findings suggest an optimization in waqf fund collection and waqf fund management.Â For waqf collection, it is important to improve public literacy and the quality and quantity of supporting facilities and systems. Meanwhile, institutional management should be strengthened for waqf management.